"The decay" of humanism, or problems of the Czech medieval literature only? - Viktora, Viktor (Bohemica Olomucensia, 2019)
The article contributes to the discussion on the issue of Czech literary humanism. The discussion critically comes to terms with the concept of this period in the first volume of "Academic" History of Czech Literature and with the synthesizing views of Milan Kopecký. One of the fundamental problems is the very definition of humanism. If a narrowed view of humanism based on its philologically-philosophical anchoring and the relation to antiquity is employed, Czech literature has to give up the 1450-1620 period, which were considered humanistic by researchers of the generation of Jaroslav Vlček, Jan Jakubec and Arne Novák, and also by the "Academic" History of Czech literature and was synthesized by Milan Kopecký. Nevertheless, it is still necessary to bear in mind the considerable volume of unexplored Latin literature of that period. In addition, our evaluation should also take into account the fact that, regarding this period, Czech literature has been compared to the so-called major European literatures - this comparison logically does not support its value. However, even the comparison with "minor" literature, which did not come to the same level, has been missing. The study analyses the term National humanism, but also the place of Viktorin Cornel of Všehrdy into literary history regarding his preface to De reparatione lapsi (Knihy o napravení padlého / The Books of Remedying the Fallen). The study also briefly recalls the scholarly interest of Eduard Petrů in this period.
Keywords: Viktorin Kornel of Všehrdy; Renaissance; Renaissance Humanism; National Humanism; History of Czech Literature